Socio-Economic Status of Women in Rural Poultry Production in Selected Areas of Kwara State, Nigeria - Ogunlade, I.; Adebayo, S.A. (International Journal of Poultry Science, 2008)
This paper examines the socio-economic status of women in rural poultry production in selected areas of Kwara State, Nigeria. This is based on the hypothesis that there is no significant relationship between women’s participation and their socio-economic status such as age, marital status, level of education and occupation. The study was conducted in selected villages in Kwara State. A total of one hundred and twenty (120) women involved in rural poultry production were interviewed using random sampling. Data collected from the study were subjected to chi-square analysis. It was discovered from this study that the ages of the women mainly ranges from 21 years to 50 years (57%-97%) across the villages. Most of the women are married (70%-100%). Many of the women have no formal education with the largest percentage at Share (63%). Majority of women involved in rural poultry production are traders (50%-73%). Most benefits enjoyed by the women through rural poultry production include income generation to buy other necessities (10%-70%), income generation for local savings (Ajo) (10%-70%), provision of meat for consumption (35%-95%), provision of meat to entertain special guests (55%-97%), provision of meat during festive seasons (55%-97%), source of gifts (50%-100%), provision of employment opportunity through the sales of egg and chicken (40% - 75%) and improvement of household diets through consumption of eggs and meats (30% - 95%). The results of the chi-square analysis showed that the variables (age, educational level, marital status and occupation) have no significant relationship with the level of participation of rural women in poultry production. From the result, it is recommended that rural poultry production should be supported and the women should be more enlightened on how to keep their birds more successfully.